EXAMINING THE EMOTION OF LOVE IN RUSKIN BOND’S SELECTED WORKS THROUGH STERNBERG’S TRIANGULAR THEORY - Fatma, Syed Mussarrat; Johri, Manjari; Srivastava, Kajal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper applies Robert J. Sternberg's Triangular Theory of Love to explore the emotional and psychological foundations of love in the works of Ruskin Bond. The study aims to uncover how intimacy, passion, and commitment evolve, intermingle, or deteriorate amid wartime tension and suspended moments by focusing on two specific texts: A Flight of Pigeons and “Time Stops at Shamli”. The findings reveal that Bond's characters often confront intense emotional attachments that are ephemeral and tragic, shedding light on the spectrum between companionate, romantic, and unfulfilled love. The study employs Sternberg's diagrammatic framework to illustrate love as a construct that collapses under the weight of silence, time, and circumstances rather than simply existing as an emotion.